Analisis Evaluasi Kebijakan Publik dalam Pengelolaan Sampah pada Dinas Lingkungan Hidup Kota Serang - Amilia, Rizki (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research was conducted in the Banten region, precisely in Serang City. This research method was conducted through literature studies and journal reviews, especially those that can be accessed online. The researcher's view is that a qualitative approach will help researchers in collecting data. This research method uses a qualitative descriptive method, where analyzing the data is described in descriptive form. According to qualitative descriptive research, which is research that seeks to describe an event in the object of research that is analyzed so as to produce a problem solution. The implementation of waste management carried out by the Serang City Government has not been fully implemented as stated in Regional Regulation Number 7 of 2021 concerning Waste Management. Based on the results of the analysis, it can be said that the policy evaluation in Serang City has not been maximized because waste management is still not maximizing the main problem.